Separation of the toxic zierin from Zollernia ilicifolia by high speed countercurrent chromatography - Coelho, R. G. [UNESP]; Calvo, T. R. [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Di Stasi, L. C. [UNESP]; Vilegas, Wagner [UNESP] (My University, 2007)
Preliminary pharmacological assays of the 70% methanol extract from the leaves of the Brazilian medicinal plant Zollernia ilicifolia Vog. (Fabaceae) showed analgesic and antiulcerogenic effects. Previous analyses have shown that this extract contains, besides flavonoid glycosides and saponins, a toxic cyanogenic glycoside. Flavonoids and saponins are compounds reported in literature with antiulcerogenic activity. In this work, we developed a methodology to separate the cyanogenic glycoside from these compounds in order to obtain enough amount of material to perform pharmacological assays. The cyanogenic glycoside zierin (2S)-β-D-glucopyranosyloxy-(3-hydroxy-phenyl)- acetonitrile was separated from the other components by high speed countercurrent chromatography (HSCCC). The solvent system used was composed of chloroform-methanol-n-propanol-water (5:6:1:4, v/v/v/v). This technique led to the separation of zierin from the possible active compounds of Zollernia ilicifolia.
Keywords: High-speed counter-current chromatography; Zierin; Zollernia ilicifolia; chloroform; flavonoid; glycoside; methanol; plant extract; propanol; saponin derivative; solvent; unclassified drug; water; zierin; zollernia ilicifolia extract; chromatography; drug structure; high performance liquid chromatography; high speed countercurrent chromatography; legume; medicinal plant; separation technique; thin layer chromatography; Fabaceae; Zollernia